The Reality of Artificial Intelligence (Al) and Its Applications in Arab Countries - Tahani Ideis (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
Artificial intelligence and robotics are the engines of the fourth industrial revolution. In the wake of the 4.0 industrial revolution, governments and businesses across the world, and especially the Arab countries, are gently shifting towards artificial intelligence and advanced technologies. In the Arab world, the UAE ranked second and ranked 36th globally. On another side, Qatar is in third place in the Arab world and ranked 42 globally. The study aims to overview the reality of Artificial Intelligence (Al) and its applications in the Arab world and emphasis Palestinian reality. The study adopted the descriptive approach, by inferring and analyzing studies, research, books and periodicals related to its subject. The present research has highlighted a few strategies, recommendations and perspectives needed urgently to transform our daily life in the Arab world. In actuality, this study examines the future of Arab peoples if artificial intelligence is adopted in various fields of life. This study seeks to analyze the adoption of Artificial Intelligence (AI) in the Arab world. Particularly, the study is important to University leaders where institutes must be equipped with the best applications of AI; also, for owners of factories and various institutions and to help them to identify the expected transformation of artificial intelligence in various fields.